Synthesis, characterization and thermal degradation kinetics of photoresponsive graft copolymers - Bezgin, F.; Demirelli, K. (Sage Publications Ltd, 2016)
A macroinitiator was prepared by copolymerization of styrene (St) with 7-methacryloyloxy-4-chloromethylcoumarone (MAOCMC). Grafting studies of coumarone with methyl methylacrylate were carried out in the presence of the macroinitiator poly(7-methacryloyloxy-4-chloromethylcoumarone-co-styrene) and with the catalyst of copper(I) bromide/2,2-bipyridyne at 110 degrees C. The activation energy valuations of graft copolymers acquired by Coats-Redfern, Tang and Flynn-Wall-Ozawa methods were designated to be 212.69, 214.44 and 223.57 kJ mol(-1), respectively. For the outcomes were compared with these valuation differential methods and discrepant integral were used. In terms of experiential outcomes, the reaction mechanism was a dimensional diffusion (Dn) deceleration type in the transformation range worked.
Keywords: Thermogravimetric analysis (TGA); coumarone; activation energy; graft copolymerization; atom transfer radical polymerization (ATRP)